SPECIFIC FEATURES OF RESOURCE TAX IMPROVEMENTS - Shukurov Sanjar (Scholar Express Journals, 2024)
Defining the function of resource tax is very important to promote the reform and perfection of resource tax. In this paper, the function of resource tax should be changed from “adjusting the differential income of resources” to “saving resources and promoting the sustainable use of resources”. According to the functional orientation of resource tax and the development and implementation of resource tax in China, it can be analyzed that although the formulation and implementation of resource tax law is of great significance, there are still some imperfections, and if we improve the tax base, adjust the tax rate, adjust the preferential policy and income distribution mechanism, we can promote the reform of the resource tax system.
Keywords: Resource Tax; Social conformity; Uzbekistan; culture